Migração e escolarização : história de instituições escolares de Tangará da Serra Mato Grosso Brasil (1964-1976) - Oliveira, Carlos Edinei de (2009)
The study ―Migration and schooling: history of educational institutions of Tangará da Serra Mato Grosso Brazil (1964-1976)‖, answers the following matter: ―How was the educational issue dealt during the encouragement of land occupation in Mato Grosso from 1960?‖ As hypothesis, we emphasize that the migrant population forced the deployment of schools, through various practices. The private settlement, called SITA, was charged the schools deployment. This research aimed to analyze the relationship between migration and schooling in Mato Grosso, approaching the following categories: time, space, student and teacher. The analyzed schools were: Rural Mixed School of Primary Education of Tangará da Serra, United Schools of Tangará da Serra, School Group of Tangará da Serra, School Group ―Dr. Ataliba Antônio de Oliveira Neto‖ and State School of Tangará da Serra. The priority was the school culture produced in these educational institutions from 1964 to 1976. The analysis was built according to Gatti Júnior and Pessanha s (2005) methodology. The thesis production carried out according to the theoretical framework of Cultural History proposed by Chartier (1990) and by Magalhães (2004). The analysis had as reference the written productions of Viñao Frago (1995); Magalhães (1998); Buffa and Nosella (1996 and 2005). The recent time history was methodologically built with the analysis of various written sources, as the press, governors message, demographics census, school documents, church records, religious congregation archives, that time legislation archives. These written sources were crosschecked with other oral and iconographic sources. After reading and analyzing these sources it was possible to conclude, confirming the initial hypothesis, that the migrant family, in a significant number, worried about their children school education process. The primary or high school in Tangará da Serra, until 1976, were built, in a first moment, from an organization performed by the migrant families that looked to a institutional support of the political and religious leaders of that place. The private settlement, in Tangará da Serra, looked after the school organization, keeping it, when it was necessary and supporting the teachers. The private settlement used the school existence as an advertisement to encourage the migration practice to Tangará da Serra. The local community mobilized itself and in eight years of migration (1960 1968) there was the basic education level and after, in 1973, the high school was organized. The state government, through its educational agencies, when the school was built up as a physical space and with human resources, made the institutionalization process keeping it in order to ensure the educational legislation.